Analysis Of Students' Needs For Differentiation-Based Arabic Language Teaching Materials/ تحليل احتياجات الطلاب لمواد تعليم اللغة العربية القائمة على التمايز - Nuriani, Rikha Ikke; Mahliatussikah, Hanik; Alfan, Muhammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This research examines the need for differentiation-based Arabic language teaching materials. Using a qualitative case study approach, the study was conducted through eight weeks of classroom observation and a Likert-scale questionnaire. The study subjects were 57 fourth-grade students at SDIT Mutiara Insani Batam, Indonesia. The results revealed a significant gap between existing teaching materials and students' needs, with a gap analysis of 0.94. The findings showed students' diverse learning styles: visual (42.1%), auditory (35.1%), and kinesthetic (22.8%). Technology integration received a positive response (average 4.32), with 86% of respondents wanting technology-based learning. The study also identified a high demand for interactive learning media (average 4.25) and activity-based learning (84.3%). These findings provide a basis for developing more effective and inclusive Arabic language teaching materials, emphasizing technology integration, learning style accommodation, and flexible content delivery systems.